PENGARUH PEMAHAMAN KODE ETIK PROFESI AKUNTAN, KECERDASAN INTELEKTUAL DAN KECERDASAN EMOSIONAL TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI DENGAN AKHLAKUL KARIMAH SEBAGAI VARIABEL MODERASI - Hendra; Sumarlin, Sumarlin; Jannah, Raodahtul (ISAFIR: Islamic Accounting and Finance Review, 2023)
This study aims to examine the effect of understanding the ethical code of the accounting profession, intellectual intelligence and emotional intelligence on the ethical behavior of accounting students with akhlakul karimah as a moderating variable. This research is a quantitative research with a causal associative approach. The sample population in this study were students majoring in Accounting class of 2018, Faculty of Islamic Economics and Business, UIN Alauddin Makassar. The sample collection technique used purposive sampling method with a total of 82 respondents. The data used in this study is primary data collected through a direct questionnaire survey. The results of this study indicate that understanding the ethical code of the accounting profession, intellectual intelligence and emotional intelligence have a significant positive effect on the ethical behavior of accounting students. Moderation analysis using the absolute difference value approach shows that the moderating variable akhlakul karimah is able to moderate the effect of understanding the code of ethics of the accounting profession on ethical behavior of accounting students but cannot moderate intellectual intelligence and emotional intelligence on ethical behavior of accounting students.